Wajah Ganda Transformasi Digital - Amandus B.S. Klau; Kristianto RM Naben; Rini Kartini (STIKes Ibnu Sina Ajibarang, 2023)
This article aims to describe the dual face of digital transformation. On the one hand, the communication and information technology revolution which has now reached the digitalization stage makes it very easy for humans to communicate and carry out their work. However, on the other hand, this progress also brings problems to humanity. By applying critical analytical studies, this research finds that the problems caused by the technological revolution are not only related to negative impacts as a consequence of the limitations and misuse of the technology, but are also related to more systemic impacts. Digital transformation has been inevitably connected to the capitalist system and the way how market works, which in practice makes the majority of humanity mere objects of exploitation and alienation. Recognizing this serious problem, this research also recommends that the ongoing technological revolution be addressed more critically and wisely.